2017
DOI: 10.9755/ejfa.2017-01-229
|View full text |Cite
|
Sign up to set email alerts
|

Variabilty of Oil and Protein Content in Rapeseed Cultivars Affected by Seeding Date

Abstract: The aim of this study was to determine the variability of oil and protein content in winter rapeseed cultivars affected by seeding date. Four cultivars (Banaćanka, Slavica, Express, Valeska) were sown at six seeding dates (SD1-21 August, SD2-31 August, SD3-10 September, SD4-21 September, SD5-1 October, SD6-9 October) across two cropping seasons. The trial was arranged as Randomized Complete Block Design (RCBD) with four replications. Analysis of variance (ANOVA) showed that the effect of year, cultivar and see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…The oil content from wheat bran (3-5%) or germ (7-9%) is much lower than that from main oil crops, such as sunflower (46%), safflower (32%), rapeseed (39%), soybean (20%), and linseed (34%). Also, the protein content of wheat (11-18%) is lower but better comparable with those reported for some conventional oil and protein crops like safflower (29.3%), sunflower (19.5%), peanut (30.3%), and rapeseed (21.5%) [42][43][44].…”
Section: Genotypic Variationssupporting
confidence: 72%
“…The oil content from wheat bran (3-5%) or germ (7-9%) is much lower than that from main oil crops, such as sunflower (46%), safflower (32%), rapeseed (39%), soybean (20%), and linseed (34%). Also, the protein content of wheat (11-18%) is lower but better comparable with those reported for some conventional oil and protein crops like safflower (29.3%), sunflower (19.5%), peanut (30.3%), and rapeseed (21.5%) [42][43][44].…”
Section: Genotypic Variationssupporting
confidence: 72%
“…In terms of climate parameters such as temperature, day length and rainfall, sowing date is one of the most important crop management for best yield. Many studies emphasized that sowing date significantly affected rapeseed yield (Johnson et al, 1995;Turhan et al, 2011;Balalic et al, 2017) and late sowing of rapeseed in winter type decreased seed yield (Pritchard et al, 2000;Ozer 2003;Uzun et al, 2009). It was concluded that rapeseed could be planted during the October-November period in the coastal zone of the Aegean region with a mild Mediterranean climate.…”
Section: Results and Discussion Seed Yield (T/ha)mentioning
confidence: 99%
“…In our study, the crude oil rate varied from 39.75% to 45.13% depending on cultivars, sowing dates and years (Figure 2). The cultivar, crop management and the environment affected the oil rate of rapeseed in which it is grown and, the oil content of rapeseed changed was between 40.0% and 44.0% (Anonymous, 2014;Balalic et al, 2017). The highest crude oil rate was recorded in NK Petrol cultivar (43.34-43.54%) at the first sowing date in both years.…”
Section: Oil Ratementioning
confidence: 99%
“…Rape oil is used in people's eating, for the production of biodiesel, in the soap industry, for lubricating parts in machinery assemblies, etc. After grain pressing and oil extraction, oil rich cakes with proteins used in domestic animal feeding are obtained [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%